Antimicrobial Resistance and Molecular Characterization of Staphylococcus aureus Recovered from Cows with Clinical Mastitis in Dairy Herds from Southeastern Brazil - Gustavo Freu; Tiago Tomazi; Antonio F. S. Filho; Marcos B. Heinemann; Marcos V. dos Santos (MDPI AG, 2022)
Staphylococcus aureus is a contagious pathogen frequently associated with bovine mastitis in Brazil. Molecular characterization of Staph. aureus isolated from affected mammary quarters of cows with clinical mastitis (CM) can provide data on epidemiological behavior of this pathogen and antimicrobial susceptibility (AMS) assessment at the genotypic level. This study genotypically characterized Staph. aureus isolates recovered from cows with CM and determined the association of genotypes and AMS. A total of 84 Staph. aureus strains identified from affected mammary quarters of cows with CM in 13 dairy herds from Southeastern Brazil were submitted for susceptibility testing to 10 antimicrobials using the technique of minimal inhibitory concentration. The same isolates were also genotyped using the spa-typing methodology. Results showed a high genotypic similarity between the Staph. aureus isolates within and between herds, which were categorized as resistant to most antimicrobials, especially to β-lactam antibiotics. In addition, differences in AMS were observed among genotypic clusters, which may affect the efficacy of antimicrobials used to treat CM in different dairy herds.